Features of Diagnosis and Surgical Treatment of Fragment Embolism of the Right Ventricle in Mine-Blast Injuries - Rostyslav M. Vitovskyi; Kostiantyn V. Gumeniuk; Volodymyr V. Isayenko; Andii R. Vitovskyi; Olga M. Unitska; Vasyl V. Lazoryshynets (Ukrainian Journal of Cardiovascular Surgery, 2025)
Among the many types of combat injuries, particular attention is drawn to fragmentary injuries of the heart and blood vessels. In such cases, the damaging agent can be located in various parts of the heart, including both its chambers and walls. A separate category of such injuries is fragment embolism of the heart and vessels, a rare consequence of ballistic trauma. This condition involves the traumatic penetration of a foreign body (usually a bullet or fragment) into a blood vessel, which then continues to migrate along the vessel to another part of the body. The rarity and high variability of clinical manifestations of such injuries have led to a lack of established treatment or management strategies.Aim. To determine the features of the course, diagnosis and treatment of right heart fragment embolism in patients with mine-explosive injuries and to provide recommendations for surgery in such conditions.Materials and Methods. Our experience includes 72 cases of mine-blast injuries. Almost all cases involved injuries to the organs of the thoracic cavity, namely the lungs, heart, or mediastinal organs. Direct heart injuries were observed in 33 patients. Localization of fragments in the right ventricular cavity was diagnosed in 14 patients. Fragment embolism of the right ventricular cavity was observed in 4 cases, accounting for 5.8 % of the total number of patients with mine-blast injuries. All were men aged 24, 29, 43, and 44 years. The leading diagnostic method that enabled detection of the fragment was contrast-enhanced CT with synchronization.Results. As a result of mine-blast fragment injuries, all 4 patients were wounded in the upper or lower limbs and inguinal region. No breaches of the chest cavity or diaphragm were observed. In all cases, fragments were found in the right ventricular cavity. Diagnosis of cardiac fragment presence was made at different times after injury, ranging from 1 day to 4 months. All patients underwent surgery using cardiopulmonary bypass via a trans-tricuspid approach. In all cases, there were no signs of pericardial injury, inflammation, hemopericardium, or damage to the cardiac walls. A neodymium magnet was used during each operation.Conclusions. The entry of fragments into the venous vessels of the upper and lower limbs may be accompanied by migration to the right heart chambers, with potential fixation to the trabeculae of the right ventricle and risk of entry into the pulmonary artery basin. Contrast-enhanced CT allows for precise localization of the fragment and aids in planning the treatment strategy. In our opinion, to prevent fragment migration into the pulmonary artery system, priority should be given to the removal of fragments located in the RV cavity.